Is serum bilirubin associated with the severity of Guillain–Barré syndrome?. (3rd July 2018) - Li, Xiaohong; Li, Wenchao; Shi, Xiang; Mo, Lijun; Luo, Yuzhen; Qin, Liuqun; Yang, Zheng; Mo, Wuning
ABSTRACT: Objective: Our aim was to assess the correlation between serum bilirubin levels and Guillain–Barré syndrome (GBS). Patients and methods: One hundred and one newly diagnosed patients with Guillain–Barré syndrome and 111 healthy age- and sex-matched individuals in the First Affiliated Hospital of Guangxi Medical University (Guangxi, China) from June 2012 to May 2017 were included in this study. Clinical characteristics and laboratory parameters of Guillain–Barré syndrome patients and healthy controls were retrospectively analysed. Results: Serum bilirubin levels in Guillain–Barré syndrome patients were significantly lower as compared with those in healthy controls ( p < 0.001); besides, log C-reactive protein and erythrocyte sedimentation rate were significantly higher. We found that there was a negative correlation between GBS disability scale scores and total bilirubin, direct bilirubin, indirect bilirubin ( r = −0.541, P < 0.001; r = −0.403, P < 0.001; r = −0.526, P < 0.001), respectively. Among patients with GBS, serum total bilirubin, direct bilirubin, and indirect bilirubin levels were independently associated with Guillain–Barré syndrome disability scale scores in multiple linear regression analysis, respectively. Conclusions: We observed that serum bilirubin levels were lower in patients with Guillain–Barré syndrome, and suggested total bilirubin, direct bilirubin, and indirect bilirubin were independently and inversely associated with Guillain–Barré syndrome severity.